2018
DOI: 10.2460/ajvr.79.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of two florfenicol formulations following intramuscular and subcutaneous administration to sheep

Abstract: OBJECTIVE To compare the pharmacokinetics of 2 commercial florfenicol formulations following IM and SC administration to sheep. ANIMALS 16 healthy adult mixed-breed sheep. PROCEDURES In a crossover study, sheep were randomly assigned to receive florfenicol formulation A or B at a single dose of 20 mg/kg, IM, or 40 mg/kg, SC. After a 2-week washout period, each sheep was administered the opposite formulation at the same dose and administration route as the initial formulation. Blood samples were collected immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…On the basis of our research, the average drug loading is 11.78% ± 0.04%. Moreover, the prepared FF-HP-β-CD was observed to have a highly enhanced solubility of 78.93 ± 0.42 mg/mL at 37 °C, which is 35.4-fold compared with FF (2.23 ± 0.04 mg/mL) and is more than the reported solubility of 40.76 mg/mL 9 .…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…On the basis of our research, the average drug loading is 11.78% ± 0.04%. Moreover, the prepared FF-HP-β-CD was observed to have a highly enhanced solubility of 78.93 ± 0.42 mg/mL at 37 °C, which is 35.4-fold compared with FF (2.23 ± 0.04 mg/mL) and is more than the reported solubility of 40.76 mg/mL 9 .…”
Section: Resultsmentioning
confidence: 78%
“…The pharmacokinetics of FF has been previously studied in animal species, including rabbits, rats, dogs, carp, swine, and sheep 9,14–17 Species differences in FF elimination exist. One-compartment open, two-compartment open, and non-compartment models exist after intravenous, intramuscular, and oral administrations in different species 18,19 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Florfenicol has less toxicity and better antibacterial activity than chloramphenicol or thiamphenicol [4,11,24]. The pharmacokinetic properties of florfenicol have been documented in many animal species [1,2,9,22,28,30], and several studies have reported on the possible metabolic pathways and mechanisms of florfenicol in vivo. Liu et al [18] reported that P-gp and/or cytochrome P450 3A (CYP3A) are likely involved in the distribution of florfenicol in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Florfenicol has low toxicity and better antibacterial activity than does chloramphenicol or thiamphenicol [3,12,25]. The pharmacokinetics of florfenicol has been documented in many animal species [1,2,6,22,29,32]. A few studies have also reported on the possible metabolic pathways and mechanisms of florfenicol in vivo.…”
Section: Introductionmentioning
confidence: 99%